Bistatic radar signature of buried landmines - Lombardi, Federico; Griffiths, Hugh D.; Balleri, Alessio (Institution of Engineering and Technology (IET), 2017)
With the proliferation of low-intensity conflict, landmines have proven to be one of the weapons of choice for both government and guerrilla forces around the world. Recent improvements to mine technology pose increasingly significant problems for demining operations, requiring the constant upgrading of countermine technologies. Ground Penetrating Radar (GPR) is one of the most exhaustively researched topics in the detection of buried mines as it can be used to detect non-metallic and plastic mines. However, identification and recognition are still unsolved problems, due to the scattering similarity between mines and clutter objects. This study provides an experimental evaluation of the improvements that a bistatic approach could yield and what can be gained from investigating the angular dependencies of the landmine radar signature.